Excess Asset Reversions and Shareholder Wealth: A Comment. - Moore, Norman H; Pruitt, Stephen W (Journal of Finance, 1990)
This study reexamines the earlier finding of Michael J. Alderson and K. C. Chen (1986) that financial markets do not consider excess pension assets in determining share prices and that significant increases in shareholder wealth occur when an overfunded pension plan is terminated. The results document that specific event-time contamination (corporate restructuring announcements) provides the driving force for all the earlier findings.